PROBLEMS FACED BY THE STAFF OF LOKAWISATA BATURRADEN IN USING ENGLISH - Pratama, Aditya Pandu; Hadiningrum, Indriyati; Puspitasari, Indah (Jurnal Vokasia, 2022)
Tourism in Indonesia develops from time to time to attract foreign tourists with various types of tourist attractions. Currently the most visited tourist attraction and a favorite of tourists is nature tourism. Lokawisata Baturraden is located in Dusun I Karangmangu, Kec. Baturaden, Kab. Banyumas, Central Java.The purposes are to find out the difficulties in serving foreign tourists, the obstacles, and the solutions from the staff of the foreign Lokawisata Baturraden. The method used is observation, shows that there are still tourist attractions that do not yet provide tour guides who can speak English and many tourist staff do not understand English.